2015
DOI: 10.1089/jir.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Differences and Synergistic Antiviral Effects Between Type I and Type III Interferon Signaling Indicate Pathway Independence

Abstract: The spread of acute respiratory viral infections is controlled by type I and III interferon (IFN) signaling. While the mechanisms of type I IFN signaling have been studied in detail, features that distinguish type III IFN signaling remain poorly understood. Type III IFNs play an essential role in limiting infections of intestinal and respiratory epithelial surfaces; however, type III IFNs have been shown to activate similar genes to type I IFNs, raising the question of how these IFNs differ and their signals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…With the aid of IFNβ and IFIT2 reporter cells we also visualized the activation of these innate immune markers in infected cells, followed by the spread of antiviral activation beyond the borders of the infected region. Activation of cellular antiviral immunity was likely due to a mixture of secreted paracrinesignaling molecules, demonstrated in this experimental system to include IFNα, IFNβ, and IFNλ 1/2/3 using ELISA (Voigt and Yin, 2015). This functional antiviral cocktail may also contain other secreted paracrine-signaling antiviral factors such as ISG15, TNFct, and IP-10 (D' Cunha et al, 1996;O'Neill and Bowie, 2010;Randall and Goodbourn, 2008;Sadler and Williams, 2008), which would function together with type I and III interferons to induce the development of cellular antiviral states.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…With the aid of IFNβ and IFIT2 reporter cells we also visualized the activation of these innate immune markers in infected cells, followed by the spread of antiviral activation beyond the borders of the infected region. Activation of cellular antiviral immunity was likely due to a mixture of secreted paracrinesignaling molecules, demonstrated in this experimental system to include IFNα, IFNβ, and IFNλ 1/2/3 using ELISA (Voigt and Yin, 2015). This functional antiviral cocktail may also contain other secreted paracrine-signaling antiviral factors such as ISG15, TNFct, and IP-10 (D' Cunha et al, 1996;O'Neill and Bowie, 2010;Randall and Goodbourn, 2008;Sadler and Williams, 2008), which would function together with type I and III interferons to induce the development of cellular antiviral states.…”
Section: Discussionmentioning
confidence: 77%
“…Not only is induction of cellular antiviral states in epithelial cells after interferon treatment rapid, this effect remains potent for days to weeks after initial stimulation, independent of any other immune mechanisms. Other work suggests that these strong downstream effects may result from independent and/or synergistic interactions between multiple secreted antiviral cytokines, thus enhancing signaling effects (Voigt and Yin, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence, however, supports non-redundant functional roles for each, particularly at sub-saturating levels, which are likely more relevant to initial exposure of the respiratory mucosa to small doses of a viral pathogen contained in micro-droplets. For example, sub-saturating combinations of IFN-β and IFN-λ1 synergize towards suppression of vesicular stomatitis virus in vitro (Voigt and Yin, 2015), and additively enhance and sustain expression of many ISGs (Novatt et al, 2016). In RSV infection of MDDCs, using B18R to block type I IFNs (Figure 5), we have shown that the majority of ISG induction relies on the presence of type I IFNs, however this does not exclude the possibility that optimal ISG expression requires -α, -β and -λ IFNs in combination.…”
Section: Discussionmentioning
confidence: 99%
“…While the antiviral programs induced by type I and type III IFNs exhibit substantial overlap (20)(21)(22) (Figure 1), a critical difference between the two is the cell types they affect secondary to receptor expression. The IFN-λ receptor consists of IFNLR1 and IL10Rβ.…”
Section: Figure 1 | Effects Of Interferon-lambda (Ifn-λ) On Viruses Imentioning
confidence: 99%